The Future Role of Cardio-oncologists - Pudil, Radek (Cardiac failure review, 2017)
Cardiovascular (CV) disease and cancer remain the two most common causes of mortality in developed countries; however, progress in the treatment of malignant diseases significantly improved survival of oncological patients. Similarly, there is an increased number of the patients with malignancy who have a history of CV disease or an increased CV risk. Rates of CV problems from cancer-related therapeutics are high, and cardiotoxicity is the second most common cause of morbidity and mortality in cancer survivors. Therefore, there is a need for the development of an efficient programme to manage the problem of cardiotoxicity with the aim to decrease morbidity and mortality in patients and to improve their quality of life. For this purpose, cardio-oncological clinics should be an essential part of the strategy.
Keywords: risk factors; management; detection; Cardiotoxicity; cardio-oncology clinic